Characterization and assessment of tailings and wastewater from small-scale mining activities along Ambalanga River - Relucio, Ian Keith R.; Angeles, Juan Rafael M.
Heavy metal contamination of aquatic and terrestri al ecosystem is one of the major environmental problems in the world. A major factor to the increasing amount of heavy meta ls in the environment is the effluent coming from mining. Mining is one of the leading industry in the economic growth of the Philippines. The Benguet Mining District in the Benguet Province is one of the leaders in the Philippine mining industry. One of the rivers in Itogon, Benguet, Ambalanga River, was found to be affected by the effluents coming from the Benguet Mining District. For this study, it aimed to characterize and assess the wastewater and tailings from the small scale mining activities along Ambalanga River. It was done by identifying the locations of the small scale mining activities along the river, obtaining the physical and chemical properties of the wastewater and tailings sample, quantifying the amount of mining wastewater discharged to the river, and comparing the gathered data to established data. Three mining sites were identified along the river, two in Brgy. Acupan and one in Sitio Maligaya. Due to the dry wastewater pool in Sitio Maligaya, there were only four wastewater samples and seven tailings samples. Samples taken from the sites were subjected to physical and chemical property tests. For the heavy metal concentrations of the samples, Metalyser HM2000 was used. All the subjects were tested for three metals namely mercury, lead, and arsenic. For the wastewater samples, while the lead and arsenic conce ntrations both passed the Department and Natural Resources Administrative Order 35 and Philippine Regulations on Sanitation and Wastewater Systems, not all samples passed the standards for mercury concentration. For the ta ilings samples, not all samples passed the mercury, lead, and arsenic concentration standards provided by ANZECC/ARMCANZ Interim Sediment Quality Guidelines, Ontario Ministry of Environment Screening Level Guidelines (OMEG), National Oceanic and Atmospheric Administration (NOAA) Sediment Quality Guidelines, and Florida Department of Environmental Protection (FDEP) Guide lines. A conclusion can be made however that mercury attaches itself to the dissolved solids and lead and arsenic attaches to the tailings. Also, arsenic and lead might come from the same source.